2014
DOI: 10.3389/fnhum.2014.00861
|View full text |Cite
|
Sign up to set email alerts
|

Epidural electrocorticography for monitoring of arousal in locked-in state

Abstract: Electroencephalography (EEG) often fails to assess both the level (i.e., arousal) and the content (i.e., awareness) of pathologically altered consciousness in patients without motor responsiveness. This might be related to a decline of awareness, to episodes of low arousal and disturbed sleep patterns, and/or to distorting and attenuating effects of the skull and intermediate tissue on the recorded brain signals. Novel approaches are required to overcome these limitations. We introduced epidural electrocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Other human studies aimed to identify cortical states over the course of the progression of amyotrophic lateral sclerosis, using low frequencies recorded with epidural grids. Among other results, they described three state‐dependent frequency domains (<4 Hz for sleep‐like periods, ~7 Hz for low arousal and ~20 Hz for elevated arousal) (e.g., Martens et al, 2014), showing for the first time the usability of epidural ECoG to detect cortical states in individuals with complete paralysis.…”
Section: Signal Decodability For Epidural Recordingsmentioning
confidence: 87%
See 3 more Smart Citations
“…Other human studies aimed to identify cortical states over the course of the progression of amyotrophic lateral sclerosis, using low frequencies recorded with epidural grids. Among other results, they described three state‐dependent frequency domains (<4 Hz for sleep‐like periods, ~7 Hz for low arousal and ~20 Hz for elevated arousal) (e.g., Martens et al, 2014), showing for the first time the usability of epidural ECoG to detect cortical states in individuals with complete paralysis.…”
Section: Signal Decodability For Epidural Recordingsmentioning
confidence: 87%
“…On the other hand, subdural NHP studies reported that movement‐related subdural signals remained well detectable over 2 years of implantation (Degenhart et al, 2016; Ryapolova‐Webb et al, 2014), despite the initial signal amplitude decrease during the first 300 days (Degenhart et al, 2016). In humans, Martens et al (2014) were able to identify three levels of arousal as an individual with locked‐in syndrome transitioned into complete locked‐in syndrome over the course of 6 months, whereas Benabid et al (2019) presented stable exoskeleton control using epidural ECoG in a tetraplegic patient for 2 years. Similarly, click‐based decoding performance in an individual with locked‐in syndrome implanted with subdural ECoG remained stable over 3 years (Pels et al, 2019).…”
Section: Longevity Of Epidural Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidural arrays, however, offer a less traumatic access to intracranial brain signals, and commercially available arrays have recently been used for e.g. diagnosis of the cognitive state in locked-in syndrome (Martens et al, 2014;Bensch et al, 2014) and rehabilitation of patients after stroke (Gharabaghi et al, 2014a;2014b). In the motor system, recent studies in non-human primates showed that EFPs allow well decoding of hand and finger gestures (Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%